The Effect of Social Media Marketing and Service Quality on Customer Satisfaction of “Rpm Body Fitness” with Brand Image as an Intervening Variable - Rahmad Ageng Handoko; Kussudyarsana Kussudyarsana (Proceedings Series on Social Sciences & Humanities, 2024)
This research addresses the challenge of maintaining competitiveness and customer satisfaction in fitness centers, during the increasing popularity of fitness activities after the COVID-19 pandemic. With a study case of RPM Body Fitness, this research aims to explore the correlation of Social Media Marketing, Service Quality, Brand Image, and Customer Satisfaction. The number of samples used in this study was 104 using non-probability sampling techniques with purposive sampling methods. In this study, the tool used to analyze is the Structural Equation Model Partial Least Square (SEM-PLS) with the help of SMART PLS 4.0 software. The results of the analysis show that social media marketing has a positive and significant effect on brand image, Social media marketing does not have a positive and significant effect on customer satisfaction, Service quality has a positive and significant effect on brand image, Service quality has a positive and significant effect on customer satisfaction, Brand image has a positive and significant effect on customer satisfaction, Brand image can mediate social media marketing on customer satisfaction, Brand image can mediate service quality on customer satisfaction. RPM Body Fitness has successfully treated its customers with great customer service and optimized its social media to increase brand image and customer satisfaction.